PENGARUH KOMITMEN ORGANISASI, STRUKTUR AUDIT DAN KONFLIK PERAN TERHADAP KINERJA AUDITOR PADA KANTOR AKUNTAN PUBLIK DI PROVINSI BALI - Fransiska Mulyati Malon; Ni Nyoman Sri Rahayu Trisna Dewi; Komang Adisanjaya (Universitas Triatma Mulya, 2021)
The aim of this study is to determine the effect of organizational commitment, auditstructure and role conflict on auditor performance in public accounting firms in BaliProvince. The sampling method used was purposive sampling method, while the datacollection method was carried out using a questionnaire. The number of samples usedin this study were 40 respondents. The data analysis technique used is multiple linearregression analysis techniques. The results of this study indicate that organizationalcommitment has a positive impact to auditor; the higher commitment of auditor in apublic accounting affect to the credibility of its performance. Audit structure has apositive impact on the performance of auditors which indicates that the more auditstructure in a public accounting firm will affect the performance of the auditor. Roleconflicts have a positive impact on the performance of the auditor. This shows that theperformance of the auditor tends to increase the higher the role conflict that the auditoris granted in an accounting firm.